Exploring L2 Listening Instruction, Self-Efficacy, and Strategy Use: A Mediation Analysis - Xu, Jian; Fan, Jason; Luo, Kaizhou (Frontiers in Psychology, 2021)
This study aims to investigate different types of English listening instruction, listening self-efficacy, and listening strategy use, particularly the mediating role of self-efficacy between listening instruction and strategy use. We first examined the types of L2 instruction being employed in English as a Foreign Language (EFL) listening classrooms and then we looked into the relationships between L2 listening instruction, listening self-efficacy, and listening strategy use. The result of exploratory factor analysis demonstrated four types of English listening instruction: process-based instruction, comprehension-based instruction, self-regulation-based instruction, and strategy-based instruction. The results of structural equation modelling showed that listening self-efficacy mediates the relationship between strategy-based instruction and listening strategy use, and self-regulation-based instruction and listening strategy use. This study has implications for understanding the effectiveness of different listening teaching practices on self-efficacy and strategy use.